EQUILIBRIUM MODULE DEVELOPMENT BASED MULTIPLE REPRESENTATIONS - chairunnisa chairunnisa; Noor Fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research aims to produce chemical equilibrium module based multiple representations. The research method used is the Research and Development. Subject of this study were 1 chemistry teachers and 20 students of the 2nd grade in 1st state high school Bandar Lampung. The trial results showed that the content of the module is limited in accordance with the curriculum. The presentation of the material in the module has excellent views of the sequence of the material presented, how the presentation of the material, symbolic representation, submicroscopic and macroscopic pre-sented and the questions that have been in accordance with the material and learning objectives. Physically, the modul is a good representation of multiple views of the font size, the separation between paragraphs, layout, use font variations (bold, italic, capital) and color selection. The test results readability aspect above 75% (Strong), or can be said to be good. Keywords: modules, chemical equilibrium, multiple representations